Interventions related to cardiovascular complications in people hospitalized by covid-19: a scoping review - José Hiago Feitosa de Matos; Emiliana Bezerra Gomes; Natália Pinheiro Fabricio Formiga; Maria Naiane Rolim Nascimento; Gabriela de Sousa Lima; Thereza Maria Magalhães Moreira (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To describe the scientific evidence of complications and the need for cardiovascular interventions in people hospitalized by Covid-19. Method: a scoping review carried out according to The Joanna Briggs Institute recommendations, in the MEDLINE, CINAHL, SCOPUS and Web of Science databases. Results: A total of 11 published studies from December of 2019 to April of 2020, presenting low levels of evidence were selected. The evidence described the myocardial injury as the most common cardiac complication reported in Covid-19, reported in approximately 8% to 12% of all severe individuals, with indications for oxygen therapy interventions, thrombotic disorders prevention and treatment, hemodynamic monitoring and assessment tests of cardiac function’s performance, along with biochemical markers of myocardial injury, yet not addressing nursing interventions. Conclusion: Cardiovascular complications and interventions have not shown consensus on the found evidence, requiring causal analysis by explanatory studies that support multi-professional clinical protocols in health.